(untitled) (Filološke studije, 2019)
This paper analyses the author whose literal work is reaction to issues of identity which are difficult to answer. Miljenko Jergović’s opus is not a search for answers and explanations (there are no indications in the text that the author has ambition to give any kind of answer), but attempt to find own peace in the social – cultural climate which demands commitment, and is, paradoxically, established on three (or even more) identities grown together. Jergović brings to light false stability and strict limitation of identity, occasionally laughing at their illusion, separation and exclusiveness. He uses irony that breaks the boundaries between identities, plays with their so-called self-sufficiency through short and effective examples of personal names. In Jergović’s poetic, that symbol of identity is a way of proving inability to separate identities. When the question of personal tragedy, which comes from confrontation of identities, becomes too painful to answer by irony, Jergović will reach for nostalgic and peaceful scene of Dalmatia, idealizes area without confrontations. That is how this author finds his way out from enchanted circle of questions without answers – in irony and Dalmatia. Because, laugh and salty air is the best way to heal wounds caused by cruel nonsense of hate and war.